2008
DOI: 10.1136/jnnp.2008.157875
|View full text |Cite
|
Sign up to set email alerts
|

Social dysfunctioning after mild to moderate first-ever stroke at vocational age

Abstract: Background: With improvements in stroke treatments,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 38 publications
2
50
0
Order By: Relevance
“…912 The percentage of individuals who were working before their stroke who return to work after stroke varies widely across studies, from 20% 913 to 66%. 914 This stems from large differences in sample characteristics, healthcare and social system differences in different countries, various definitions of work, and variable follow-up periods. It is clear, however, that a large percentage of individuals with stroke who are of vocational age do not return to work.…”
Section: Return To Workmentioning
confidence: 99%
“…912 The percentage of individuals who were working before their stroke who return to work after stroke varies widely across studies, from 20% 913 to 66%. 914 This stems from large differences in sample characteristics, healthcare and social system differences in different countries, various definitions of work, and variable follow-up periods. It is clear, however, that a large percentage of individuals with stroke who are of vocational age do not return to work.…”
Section: Return To Workmentioning
confidence: 99%
“…Other studies looking at predictors of related concepts post stroke, for example, social dysfunction (Hommel et al, 2009) or participation (Desrosiers et al, 2006), may have underestimated the impact of aphasia, as they excluded people with language difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that some factors which could impact on social network were not assessed. Hommel et al (2009), for example, found that cognition, particularly working memory, was a significant predictor of a related concept, social dysfunction, post stroke. It may also be that cognitive communication disorders, as well as concepts such as self-esteem, self-efficacy and personality traits, affect social network functioning but were not assessed.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Most of the existing literature implicates increased physical disability as the main factor contributing to decreased QOL in stroke survivors even in cases of mild stroke [12,[15][16][17][18][19][20][21][22]. This is quite significant, particularly as it relates to ischemic stroke where it has been proven that patients who received intravenous recombinant tissue plasminogen activator (rtPA) within the first 3 h of stroke onset were 30% more likely to have either negligible physical disability or no disability at all [23].…”
Section: Introductionmentioning
confidence: 99%